2008
DOI: 10.1093/jpepsy/jsn129
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of the Development of Very Young Boys with Fragile X Syndrome

Abstract: Developmental delays are evident in some infants with FXS as young as 9 months of age. Pediatric psychologists need to be informed about the developmental profiles in young children with FXS to accurately diagnose, treat, and support these children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 28 publications
5
76
2
Order By: Relevance
“…Most children with FXS experience delays in expressive and receptive language Mirrett, Bailey, Roberts, & Hatton, 2004;Roberts et al, 2009), but there have been a few studies examining the roots of these language deficits. These studies on early communication development suggest that evidence for delays in language can be traced to deficits in early social communication behaviors.…”
Section: Early Language Development In Fxsmentioning
confidence: 99%
“…Most children with FXS experience delays in expressive and receptive language Mirrett, Bailey, Roberts, & Hatton, 2004;Roberts et al, 2009), but there have been a few studies examining the roots of these language deficits. These studies on early communication development suggest that evidence for delays in language can be traced to deficits in early social communication behaviors.…”
Section: Early Language Development In Fxsmentioning
confidence: 99%
“…Similar patterns have been observed through examiner ratings of naturalistic interactions at the beginning and end of research assessments. Compared with TD controls, individuals with FXS have shown atypical overall social approach behaviors, as measured by facial expression, eye contact, and physical movement (Roberts, Mankowski, et al, 2009; FXS mean age = 3.99 ± 2.25 yeqrs). Consistent with findings in older children (Hall et al, 2009), young children with FXS have shown improvements in approach behaviors over the course of assessments, suggesting a “warm up” effect after initial periods of social anxiety.…”
Section: Anxiety In Fxsmentioning
confidence: 99%
“…Several studies have begun laying the foundation for this work by characterizing early features of the FXS phenotype relevant to anxiety, such as atypical social approach (e.g., Hall, Lightbody, Huffman, Lazzeroni, & Reiss, 2009; Hessl, Glasser, Dyer-Friedman, & Reiss, 2006; Roberts, Mankowski, et al, 2009; Roberts, Weisenfeld, Hatton, Heath, & Kaufmann, 2007) and physiological arousal (e.g., Hall et al, 2009; Roberts, Boccia, Bailey, Hatton, & Skinner, 2001, Roberts, Tonnsen, Robinson, & Shinkareva, 2012). These studies suggest the expression of anxiety and other challenging behaviors in FXS may be partially attributed to atypical arousal modulation (Cornish et al, 2004; Hessl, Rivera, & Reiss, 2004).…”
mentioning
confidence: 99%
“…Measures of anxiety, attention, and hyperactivity are highly associated with other behavior problems (29). There is evidence that autism scores decreased with time, particularly in communication and social aspects of adaptive behavior (57). However, emotional symptoms, behavioral difficulties, problems with peers and social behaviors may remain relatively stable over time (58).…”
Section: Behavioral Phenotypementioning
confidence: 99%